The sum of all fears [videorecording (DVD)] - Robinson, Phil Alden; Affleck, Ben, 1972-; Freeman, Morgan; Cromwell, James; Schreiber, Liev; Moynahan, Bridget, 1972-; Bates, Alan, 1934-2003; Hinds, Ciarán, 1953-; Hall, Philip Baker, 1931-; Rifkin, Ron; Clancy, Tom, 1947-2013 (Paramount Pictures, 2002)
CIA agent Jack Ryan finds himself in a race against time to stop terrorists who plan to ignite a war between the U.S. and Russia by detonating a nuclear bomb at the Super Bowl game.